A Review of Cordia Species Found in the Caribbean: Cordia Obliqua Willd., Cordia Dichotoma G. Forst. And Cordia Collococca L. (14th September 2020) - Aimey, Zoie; Goldson-Barnaby, Andrea; Bailey, Dennis
ABSTRACT: Members of the Cordia genus possess medicinal properties. There is however limited scientific literature on species within the genus that exists in the Caribbean, namely Cordia obliqua Willd., Cordia dichotoma G. Forst. and Cordia collococca L. This paper provides an overview of these plant species based on their morphology, growth conditions, fruiting season, nutritional and medicinal properties, current processing methods as well as their potential applications in the food and pharmaceutical industries.